Critical need to enahnce yield and labour output to assure sustainability of rubber plantations in Malaysia - Chandran M R (Proceedings of Seminar on Low Intensity Tapping Systems(LITS) 10 August 1998, Training Complex, Sungei Buloh. pp.3-16)
Natural rubber as a raw material has been facing low prices for over 10 years, and the situation is exacerbated by the current currency crisis in the major producing countries. The continuing low prices of rubber have meant that the capital inflow needed to develop or maintain rubber plantations in Malaysia is less attractive to investors. As a consequence there has been a decline in area under rubber; this to an extent is also applicable to the smallholder sector. Even with a scale price of RM 3.50/kg (for premium grades of processed rubber) high yielding estates (1500-1600 kg/ha/year) obtain profits which are very much less than obtainable from an average yielding (22 tonnes FFB/ha) oil palm area. An added disincentive is the low labour productivity under the conventional d/2 and d/3 systems of tapping. The newly introduced Low Intensity Tapping System (LITS) is an avenue to increase productivity or more to answer the problem of acute shortage of labour. There is an urgent need to increase production efficiency through improved clones with much higher productivity and improved exploitation systems with more trees tapped and higher productivity per man day.
Keywords: Malaysia; Rubber plantations; Yield